Self-Healing in Islamic Spirituality: Bridging Hamka’s Tafsir Al-Azhar with Modern Psychological - W, Via Sinta Mukharomah; Ida Kurnia Shofa (Faculty of Ushuluddin and Philosophy, 2023)
The concept of self-healing has become a rapidly growing social discourse, in line with socio-cultural changes influenced by capitalism and technological advances. Capitalism encourages individuals to exceed physical and mental limits in pursuit of professional achievement, leading to accumulated stress and mental health disorders. On the other hand, technological advances have facilitated access to information that can exacerbate social comparisons. Although the term self-healing is often associated with temporary activities such as vacationing or shopping, these often only provide momentary happiness without delving into spiritual healing. This article examines the concept of self-healing in Hamka’s Tafsir al-Azhar, which integrates spiritual dimensions into religious practices such as dhikr, prayer, patience, and gratitude. This study uses a qualitative approach with textual analysis to link Hamka's understanding of spiritual healing with contemporary psychological concepts such as mindfulness, emotional regulation, and gratitude. The results of this study indicate that Hamka’s approach to self-healing can build a dialogue between Islamic spirituality and modern psychological methods, opening up the potential for developing a more comprehensive and applicable approach to spiritual healing for contemporary Muslim communities.